Review: magnetically assisted resistance spot welding. (2nd January 2016) - Li, Y. B.; Li, D. L.; Lin, Z. Q.; David, S. A.; Feng, Z.; Tang, W.
Abstract : Currently, the use of advanced high strength steels (AHSSs) is the most cost effective means of reducing vehicle body weight and maintaining structural integrity at the same time. However, AHSSs present a big challenge to the traditional resistance spot welding (RSW) widely applied in automotive industries because the rapid heating and cooling procedures during RSW produce hardened weld microstructures, which lower the ductility and fatigue properties of welded joints and raise the probability of interfacial failure under external loads. Changing process parameters or post-weld heat treatment may reduce the weld brittleness, but those traditional quality control methods also increase energy consumption and prolong cycle time. In recent years, a magnetically assisted RSW (MA-RSW) method was proposed, in which an externally applied magnetic field would interact with the conduction current to produce a Lorentz force that would affect weld nugget formation. This paper is a review of an experimental MA-RSW platform, the mode of the external magnetic field and the mechanism that controls nugget shape, weld microstructures and joint performance. The advantages of the MA-RSW method in improving the weldability of AHSSs are given, a recent application of the MA-RSW process to light metals is described and the outlook for the MA-RSW process is presented.